CONTROLLING THE HOUSEHOLD ELECTRICITY LOAD THROUGH COMPUTERS AND SMARTPHONES - Syaiful Amri; Wenny Wahyuni (Merdeka Malang University, 2019)
Electricity consumption in the world is getting more massive with limited amount of fuel and its expensive price, not to mention the rising of electricity rates (the revocation of subsidy electricity). Therefore, it requires alternative solutions to tackle on energy crisis. One of the ways to save electrical energy is by turning off unutilized electrical appliances. Automation is highly required in daily lives especially in this modern age that demands more effectiveness and efficiency in daily activities. Oftentimes, one forgets about some tiny actions such as turning off the lamps dispenser, fans, air conditioners and any other electrical appliances. These actions cause electrical energy waster due to electricity consumption negligence. In order to avoid electrical energy waste, it requires an easy and effective electricity load control system. Relay Driver is utilized as an intermediary thus the main computer is able to control actuator with an on/off switch. Electrical appliances are able to be controlled over an application in an android smartphone as well as in a computer which are connected to internet through a wireless connection (WiFi) by tapping a menu feature in the application in order that it can be accessed automatically and can be controlled manually and borderlessly. The maximum range that can be detected by TP-Link Wireless N Router TL-WR841N is 75 meter.DOI : https://doi.org/10.26905/jeemecs.v2i2.3286